Comic-Polya Method Integration in Physics: Enhance Students' Conceptual Understanding and Motivation - Charmagne Kris C. Gardose; Arlene A. Castillo; Melvin H. Madroñal (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Filipino students' declining science performance calls for innovative instructional methods. This study evaluated the effects of integrating comic-based instruction and the Polya Method in Grade 8 Physics lessons at Opol National Secondary Technical during the 2023–2024 school year. Methodology: Thirty-six students were selected using convenience sampling. Employing a mixed-method approach, this study used a one-group pre-test and post-test design and focus-group discussions for qualitative data. Conceptual understanding and science motivation were assessed over one month using a 30-item pre- and post-test aligned with the Department of Education competencies. Main Findings: Pre-test results from 86.11% of students who needed improvement categories were high. After the intervention this percentage distribution decreased to 13.89%, with improvements in the categories of satisfactory (30.56%) and outstanding (13.89%). Qualitative analysis indicated increased science motivation (moderately high to high), and thematic analysis revealed enhanced engagement, enjoyment, academic performance, and problem-solving skills. Post-intervention, mean test scores rose from 11.31 to 19.69 (t = 13.786, P = 0.0001), demonstrating the effectiveness of combining comic-based learning with Polya's method. Novelty/Originality of this study: This research presents newly gained perspectives on incorporating comic-based learning and the Polya Method to enhance the conceptual understanding and science motivation of Filipino secondary students in selected Physics lessons. Thematic analysis unveiled three unique themes that contribute to the science education research literature focused on the Philippines and these strategies.